When “Too Much and Too Slapdash” No Longer Satisfies: Existential Changes Brought by Altering the Speed of Life - Pivoriūtė, Milda; Poškauskaitė, Karolina (Sociologija. Mintis ir veiksmas, 2019)
This article uses two opposing concepts of time to articulate the tensions that are common among the working-age urban population of today’s post-industrial societies and their solutions at the individual level. The importance of the time dimension for the analysis of today’s people’s lives is revealed through the analysis of sociological studies of the concepts of fast and slow time and the results of a qualitative study which included interviews with 18 people who linked their changes in life to different regimes of time. For some people who live in fast-time mode, turning back to slow time becomes an essential principle for achieving significant existential changes that lead to a subjectively more meaningful, qualitative, freer, and more authentic life.
Keywords: acceleration society; high-speed society; time pressure; fast time; slow time; sociology of time; existential changes